International financial reporting standards and financial reporting quality among Nigerian listed companies - Musa, Auwalu (2015)
This research investigates International Financial Reporting Standards (IFRS) and financial reporting quality among Nigerian listed companies. The research focused on qualitative characteristics of financial reporting (value relevance and timeliness). The study determined the financial reporting quality of 77 sample companies listed on Nigerian stock exchange. The study was limited to one year financial statement, which used UUM-Data stream in collecting the relevant data. The regression result of value relevance of financial reports reveals that there is a positive and significant relationship between stock price with book value of equity and net income after the adoption of IFRS. Similarly, timeliness of financial information regression results also revealed that return on assets and returns on equity are positive and significantly associated with stock returns after IFRS adoption in Nigeria. The findings implied that the financial reporting of Nigerian listed companies were value relevant and timelier after the adoption of IFRS. The significant positive relationship between accounting measures on stock price and stock returns shows that investors’ can predict future market value of individual securities, as the efficient market theory posits that securities prices disclose a significant amount of information from many different sources in the securities market and important current financial information of companies. Investor receives considerable information simply by knowing the price information on time which found more value relevant